Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.17582/journal.aavs/2018/6.3.139.147
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Efficacy of Verticillium lecanii and Beauveria bassiana of Commercial Source Against Cattle Tick, Rhipicephalus (Boophilus) annulatus

Abstract: T icks are an important threat to livestock due to either their direct effect or their role as tick-borne diseases. The ticks control is commonly by using chemical products, which has several side effects. Therefore, using biological control agents has become urgent and safe alternative to reduce and to avoid these adverse effects (Samish et al., 2004; Reis-Menini et al., 2008). Entomopathogenic fungi were commonly used in pest control of crops and forest pests (Kaaya et al., 1996). Recently, great attention i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…(Šebesta et al, 2022). non-target effects V. lecanii is a suspended fungus that contains enzymes that help the fungus penetrate the shell of insect eggs and cause the death of the embryos inside it (Damialis et al, 2015), while another study (Aboelhadid et al, 2018), confirmed that exposing Rhipicephalus annulatus eggs to V. lecanii spores at a concentration of 1*10 1 spore/ml did not significantly affect the hatching rate of these eggs. A study (Abdullah et al, 2009) indicated that exposing the eggs of C. pipiens of B. bassiana spores at a concentration of 3*10 5 spore/ml led to all of them being destroyed, as for study used C. quinquefasciatus and A. pulcharhimus (Al-Karawi and Hanaa, 2012), showing that the treatment of eggs C. quinquefasciatus and A. pulcharhimus pylori spores of L. lundbergii led to their mortality by 56% and 59.33%, respectively, at a concentration of 3 *10 7 spore/ml.…”
Section: Discussionmentioning
confidence: 92%
“…(Šebesta et al, 2022). non-target effects V. lecanii is a suspended fungus that contains enzymes that help the fungus penetrate the shell of insect eggs and cause the death of the embryos inside it (Damialis et al, 2015), while another study (Aboelhadid et al, 2018), confirmed that exposing Rhipicephalus annulatus eggs to V. lecanii spores at a concentration of 1*10 1 spore/ml did not significantly affect the hatching rate of these eggs. A study (Abdullah et al, 2009) indicated that exposing the eggs of C. pipiens of B. bassiana spores at a concentration of 3*10 5 spore/ml led to all of them being destroyed, as for study used C. quinquefasciatus and A. pulcharhimus (Al-Karawi and Hanaa, 2012), showing that the treatment of eggs C. quinquefasciatus and A. pulcharhimus pylori spores of L. lundbergii led to their mortality by 56% and 59.33%, respectively, at a concentration of 3 *10 7 spore/ml.…”
Section: Discussionmentioning
confidence: 92%
“…Studies have shown that combinations of entomopathogenic fungi isolated from soil or bought from a commercial source are potential pathogens for use in the control of ticks (Szczepańska et al, 2020, Aboelhadid et al, 2018, Ren et al, 2016. Thus, in this study, we examined the in vitro acaricidal effectiveness of combined commercial strains Esporomax ® (B. bassiana, M. anisopliae and P. fumosoroseus) and Trishok ® (T. harzianaum and T. virens).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the evolutionary stage, the action of certain fungi is different. Eggs are the most sensitive and nymphs are the most resistant [115,116]. A high ovicidal action against Boophilus microplus eggs were observed in Verticillium lecanii (strains LBV-2 and LBV-1) and lower in Beauveria bassiana [117].…”
Section: Ticksmentioning
confidence: 99%